FAKTOR-FAKTOR YANG MEMENGARUHI FRAUDULENT FINANCIAL STATEMENT STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Darise, Rezky Febriendy; Kalangi, Lintje; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to detect and analyze the factors that influence Fraudulent Financial Statements using the Beneish M-Score, Fraud Pentagon Theory consisting of Pressure, Opportunity, Rationalization, Arrogance, Competence, and CEO of Narcissism in banking sector companies listed on the Indonesia Stock Exchange (IDX). This study examines the theory based on previous research and is expected to open new knowledge about the effect of fraud indicators on the occurrence of fraudulent financial statements. The research method used is a quantitative research method with the type of explanatory research where the data obtained are in the form of numbers and analysis using statistics. The data obtained is secondary data in the form of financial statements of banking sector companies listed on the Indonesia Stock Exchange from 2017 to 2019 with a total of 46 banking companies and after using the purposive sampling method there are 26 banking companies. The results of the study show that the factors that influence the Fraudulent Financial Statement contained in the Fraud Pentagon Theory and CEO Narcissism are (1) the Pressure Factor which is proxied by financial stability, external pressure, financial targets, and personal financial need, (2 ) Opportunity factor which is proxied by the composition of independent commissioners, (3) Competence factor which is proxied by change of directors, (4) Arrogance factor which is proxied by the frequency of CEO image appearance, (5) CEO Narcissism Factor which proxied by CEO compensation. Meanwhile, the factor that does not affect the Fraudulent Financial Statement is the Rationalization Factor which is proxied by the audit opinion.